Pengaruh Kepemimpinan dan Motivasi Kepala Sekolah terhadap Kinerja Guru SMP di Kecamatan Keluang Banyuasin - Suwardi Suwardi; Bukman Lian; Nila Kusumawati (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This study aims to determine the influence of principal leadership and motivation on teacher performance in public junior high schools (SMP) in Keluang District, Musi Banyuasin Regency. The background of this research lies in the crucial role of school principals as leaders who guide, direct, and motivate teachers to carry out their duties and responsibilities effectively. This study employed a quantitative approach using a survey method. The population consisted of all public junior high school teachers in Keluang District, with samples selected through proportional random sampling. Data were collected using a questionnaire that had been tested for validity and reliability. The data were analyzed using multiple linear regression to determine the effect of leadership and motivation variables on teacher performance. The results revealed that principal leadership had a positive and significant effect on teacher performance, meaning that better leadership skills in managing and directing schools lead to higher teacher performance. Likewise, work motivation had a positive and significant impact on teacher performance, indicating that highly motivated teachers tend to be more disciplined, creative, and productive in their work. Simultaneously, principal leadership and teacher motivation significantly contributed to improving teacher performance in public junior high schools in Keluang District. These findings emphasize the importance of strengthening school leadership capacity and enhancing teacher motivation as key efforts to improve the overall quality of education.